(untitled) - Ignacimuthu, S. (Harrow, UK, 2005)
Bioinformatics is a computer-asisted interface discipline dealing with acquisition, storage, management, access anf processing of biological data. Bioinformatics is useful in identifying genes in DNA sequences, in the study of structure and function of genes and protein sequences in identifying families of related sequences, in aligning similar sequences and generating phylogenetic trees, in discovering drug targets, and in drug development.
Keywords: Bioinformatics,Thông tin sinh học